The why of work : how great leaders build abundant organizations that win - Ulrich, David, 1953- (McGraw-Hill, 2010)
"By following the Ulrichs' step-by-step guidelines, you will set off a chain reaction of positive and enduring effects. Employees who find meaning in their work are more competent, committed, and eager to contribute--and their contribution will result in increased customer commitment, which delivers a winning performance on the bottom line. The 'Why of Work' includes targeted checklists, questionnaires, and other useful tools to help you turn aspirations into action. Using the proven principles of abundance, you can coordinate your needs with those of your employers, your employees, and your customers--and create a vision that resonates for years to come. When you understand why we work, you know how to succeed."--Resource description page.